Revolusi Hijau: Tren Penerapan Konsep Green Infrastructure sebagai Solusi Inovatif dalam Manajemen Sarana dan Prasarana Sekolah - Bramantio Yusuf Wibarahman; Aimah, Siti (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2025)
Green Infrastructure is a concept of developing facilities and infrastructure that applies environmentally friendly principles, such as the use of renewable energy, rainwater management, and green open spaces to support sustainability. In the educational context, the implementation of Green Infrastructure not only serves as a physical element of school buildings but also plays an essential role in the management of school facilities and infrastructure to create a healthy, efficient, and climate-adaptive learning environment. This study aims to analyze the implementation of Green Infrastructure in the management of facilities and infrastructure at SMA Darussalam Blokagung, identify the management challenges faced, and evaluate its impact on environmental sustainability and learning effectiveness. The study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the school principal, facilities managers, teachers, and students, as well as document analysis of school policies related to green programs. The findings reveal that the implementation of Green Infrastructure, such as the development of educational gardens, the use of natural ventilation and lighting, rainwater management systems, and the utilization of renewable energy, has had a positive impact on students’ comfort and the school’s energy efficiency. However, limited budgets, a lack of technical understanding, and weak policy integration remain major challenges to its optimal implementation. These findings highlight the need for more strategic management planning, integrated policy support, and collaboration with external stakeholders to expand and strengthen the application of Green Infrastructure in schools.